2018
DOI: 10.1007/s40430-018-1158-9
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the rotational behaviour of a Savonius wind turbine for two-lane highway applications

Abstract: The objective of this work is to understand the behaviour of a Savonius wind turbine (SWT) on two-lane highways located in Coimbatore district, India. Experiments were conducted by placing a Savonius wind turbine (SWT) on the sides of the highway during the southwest monsoon season in three different directional roads, i.e., southwest to northeast , south to north and west to east. Vehicles moving on the highway at varying speeds modify the velocity of air locally, which in turn results in varying the drag for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In a previous study, the cut in speed of the proposed system is 3.5 m/s and the performance of the SWT system was examined in a wind tunnel and the results were discussed. 20 The total cost for fabricating a single SWT was only around $110. (Figure 4).…”
Section: Design Description Of the Proposed Swt Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, the cut in speed of the proposed system is 3.5 m/s and the performance of the SWT system was examined in a wind tunnel and the results were discussed. 20 The total cost for fabricating a single SWT was only around $110. (Figure 4).…”
Section: Design Description Of the Proposed Swt Systemmentioning
confidence: 99%
“…Since, the vehicles crossing in lanes L1 and L4 will not make any changes in rotational speeds of SWT. 20 The power output of the SWT was measured in varying wind speeds after vehicles in the lanes L2 and L3 crossed the SWT. The Estimated average vehicle traffic per 30 min in condition C at the selected geographical location is 36.…”
Section: Design Description Of the Proposed Swt Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Speeding vehicles produce a scattered wind flow with disturbances from crosswinds and other external wind sources. A study by Santhakumar et al, [5] revealed that vehicles moving in opposite directions affect the rotational speed of wind turbines and cause a negative drag force on the blades. Therefore, as an alternative, a curtain system can be placed in front of the wind turbine blades to prevent a negative torque [6].…”
Section: Introductionmentioning
confidence: 99%